2022
DOI: 10.1002/fsn3.2889
|View full text |Cite
|
Sign up to set email alerts
|

Compare with different vegetable oils on the quality of the Nemipterus virgatus surimi gel

Abstract: To enhance the quality and flavor of surimi‐based products, we investigated the effects of vegetable oils (peanut, soybean, corn, coconut, olive, and safflower seed oils) on the texture, water‐holding capacity (WHC), microstructure, and flavor of the Nemipterus virgatus surimi gel. The results showed that 6 kinds of vegetable oils could improve the whiteness and flavor of gels. However, peanut, olive, and coconut oils enriching oleic acid or lauric acid were easy to accumulate with an average diameter of more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 40 publications
0
11
1
Order By: Relevance
“…Gao et al [5], stated that the higher value of CLR causes more components, i.e., organic component and moisture, to be removed, hence the low capability of the gel in regulating immobilized water during cooking. The value of CLR found in this study (18 to 25%) was higher than in a recent study (9 to 13%) conducted by Song et al [24]. However, it was lower than that was found by Gao et al [5] who reported the CLR value of Amour sturgeon surimi gel under reducedsalt condition ranged from 6 to 42%.…”
Section: Cooking Loss Rate Of Surimi Gelcontrasting
confidence: 79%
See 2 more Smart Citations
“…Gao et al [5], stated that the higher value of CLR causes more components, i.e., organic component and moisture, to be removed, hence the low capability of the gel in regulating immobilized water during cooking. The value of CLR found in this study (18 to 25%) was higher than in a recent study (9 to 13%) conducted by Song et al [24]. However, it was lower than that was found by Gao et al [5] who reported the CLR value of Amour sturgeon surimi gel under reducedsalt condition ranged from 6 to 42%.…”
Section: Cooking Loss Rate Of Surimi Gelcontrasting
confidence: 79%
“…The cooking loss rate (CLR) was evaluated following the technique of Song et al [24]. The gels with 2.5 cm of diameter surimi gel were weighed (G1).…”
Section: Cooking Loss Rate (Clr)mentioning
confidence: 99%
See 1 more Smart Citation
“…It is difficult to mix well with other compounds during the process, due to its natural semi‐solid state. More addition of lard could lead to larger oil droplet, weaker oil holding capacity, lower gel hardness and elasticity, which further weakened the gel quality from freshwater fish (Yang, Meng, et al ., 2022; Song et al ., 2022a). Therefore, it is necessary to reduce or overcome such effect of lard on the quality of surimi‐based product by exploring an alternative processing for the application of lard.…”
Section: Introductionmentioning
confidence: 99%
“…However, pre‐emulsified oil has deficiencies in emulsification effect and stability, such as low embedding rate and instability (Florence & Whitehill, 1985). The proper amount of pre‐emulsified soybean oil and safflower seed oil could fill in the voids of soft‐shelled turtle surimi gel, resulting in a denser network structure and enhancing its quality effectively (Song et al ., 2022a, 2022b). Ultrasound could produce finer emulsification with the cavitation effects (Ding et al ., 2019; Amiri‐Rigi et al ., 2023).…”
Section: Introductionmentioning
confidence: 99%